High-performance and self-rectifying resistive random access memory based on SnO2 nanorod array: ZnO nanoparticle structure. (29th October 2019) - Liu, Qi; Li, Yang; Wang, Wenxiao; Yue, Wenjing; Gao, Song; Zhang, Chunwei; Cao, Bingqiang; Chen, Zhenxiang
Abstract: To develop high-density memory arrays, a self-rectifying resistive random access memory based on a Cu/SnO2 nanorod array: ZnO nanoparticle (NP)/fluorine-doped tin oxide (FTO) structure is proposed to avoid the sneak current. The proposed device exhibits transparent property and significant merits including high ON/OFF ratio, conspicuous endurance and superior data retention. A carrier transport model based on a SnO2 /FTO Schottky barrier, ZnO NP trap effect and Cu filament is proposed to explain the self-rectifying resistive switching performance. This work provides a new method to effectively avoid sneak current and also shows promising prospects in constructing high-performance transparent memory arrays.